Clopidogrel as an Oral Antiaggregant in Ischemic Heart Disease - Truong Dinh Cam (Journal of Global Pharma Technology, 2020)
The use of antiaggregant in preventing cardiovascular diseases remains an important therapeutic approach. The research aims to perform a comparative analysis of the effect of acetylsalicylic acid (aspirin) and clopidogrel monotherapy or their combination on platelet aggregation applying the method of impedance aggregometry. The study was carried out in 2018-2019 in Grozny (Russia) and in Ho Chi Minh (Vietnam) based on the past medical histories of 557 patients diagnosed with ischemic heart disease in 3 primary health-care facilities. The acetylsalicylic acid monotherapy in amount 100 mg per day was used for the treatment of 367 patients comprising Group I, another 147 patients (Group II) received clopidogrel in a dosage 75 mg per day, and the rest 43 patients (Group III) took both drugs. The method of impedance aggregation with the estimation of three parameters, such as platelet aggregation time, aggregation amplitude, and the area under the aggregation curve, was applied after the introduction of two inducers, namely, collaagen and ADP. In Group I, the use of collagen as an inducer resulted in prolonged platelet aggregation period and reduction of area under the curve (correlation -0.80 (p ≤0.05)). In Group II, the influence of clopidogrel on both inducers was reported. In the case of ADF-initiated platelet aggregation, a positive correlation between amplitude and area under the aggregation curve of 0.98 (p ≤ 0.01) was recorded. A correlation of 0.77 (p ≤ 0.05) was noted between the platelet aggregation extension and the area under the collagen-induced process curve. The results obtained through this research in the opposite correlation coefficients for Group I and Group II show the mechanisms of acetylsalicylic acid and clopidogrel action. The applied methodology allowed establishing qualitative and quantitative changes occurring in the aggregation of platelets with the addition of ADP and collagen as inducers. Keywords: ADP; Antiaggregant; Acetylsalicylic acid (ASA); Clopidogrel; Collagen; Ischemic heart disease.